Impact of synthetic cannabinoid use on hospital stay in patients with bipolar disorder versus schizophrenia, or other psychotic disorders. (March 2018) - Deng, Huiqiong; Mohite, Satyajit; Suchting, Robert; Nielsen, David A.; Okusaga, Olaoluwa O.
Abstract: Synthetic cannabinoid products have become popular and have led to an increased number of patients presenting to emergency departments and psychiatric hospitals. The purpose of this study was to evaluate the impact of synthetic cannabinoid use at admission on length of stay and doses of antipsychotics at discharge in individuals with bipolar disorder, schizophrenia and other psychotic disorders. We retrospectively examined medical records of 324 inpatients admitted from January 2014 to July 2015. We found that synthetic cannabinoid use predicted length of stay and antipsychotic dose using structural equation modeling. Further, the association of synthetic cannabinoid use with length of stay was partly mediated by antipsychotic dose. These associations were independent of specific diagnosis. In conclusion, patients with bipolar disorder, schizophrenia, or other psychotic disorders who reported synthetic cannabinoid use at admission had shorter length of stay and received lower doses of antipsychotics, irrespective of clinical diagnoses. Highlights: This study examined the impact of synthetic cannabinoid (SC) use on hospital stay. Patients with bipolar, schizophrenia, or other psychotic disorders were included. Patients with SC use had shorter stays and received lower doses of antipsychotics. The inclusion of clinical diagnoses did not alter this finding.